MENGGALI POTENSI THE WIPO TREATY ON INTELLECTUAL PROPERTY, GENETIC RESOURCES AND ASSOCIATED TRADITIONAL KNOWLEDGE UNTUK MEMPERKUAT PELINDUNGAN PENGETAHUAN TRADISIONAL - Tiaraputri, Adi; Daulay, Zainul; Diana, Ledy (Fakultas Hukum Universitas Islam Indonesia, 2025)
WIPO Treaty 2024 was adopted by WIPO Member States on May 24, 2024, and will enter into force three months after there are 15 ratifications and accessions. The treaty is open for signature by any eligible party for one year after its adoption, i.e. until May 23, 2025. The first WIPO Treaty 2024 recognizes the rights of indigenous peoples and local communities to their genetic resources and knowledge and their right to be included in the implementation of the treaty. Recognition of the rights of indigenous peoples such as their traditional knowledge is part of human rights. Indigenous peoples as holders of intellectual property rights. This paper is a legal research, namely normative legal research. Research that reflects on applicable norms. In addition, the research also uses literature both from books and journals as a source of research data. The normative legal research method uses a statutory approach and a conceptual approach. The articles in the WIPO Treaty 2024 that are closely related to traditional knowledge and indigenous peoples/local communities are Article 3, Article 5, and Article 6. Article 3 deals with disclosure requirements related to patents and traditional knowledge. Article 5 regulates sanctions and maintenance and Article 6 on the availability of information systems of traditional knowledge. The provisions in the WIPO Treaty 2024 do not maximize the protection of traditional knowledge, but this could be the first step towards the recognition of traditional knowledge in international agreements relating to intellectual property rights.